The Study of Emotional Problems, Self-Emotional Regulation Problems, and How the Positive Psychology and Collaborative Learning Approach can be Implemented in Enhancing Self-Emotional Regulation Ability of Chinese Students - Zhu, Yan; Henry Yuh , Anchunda; Kaewurai, Wareerat (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were 1) to study Chinese university students’ emotional problems and self-emotional regulation problems and 2) to study how the positive psychology theory and collaborative learning approach can be implemented to enhance university students’ self-emotional regulation ability. The research involved 100 freshmen from five majors at Guangxi University of Science and Technology, China, along with four experts. Data were collected through structured interviews validated by five experts and analyzed using content analysis. The findings reveal that students commonly experience emotional problems such as confusion about the future, anxiety, social anxiety, self-blame or guilt, low self-esteem, frustration, depression, and irritability. The personal problems that students faced were that they were not good at regulating negative emotions in terms of situation modification, attention deployment, and choosing positive strategies. Students also faced teacher-related problems, such as teacher-centered methods of theoretical lecturing and a lack of opportunities to practice emotional regulation in the classroom. Some students also reported that they were reluctant to participate for fear of ridicule from the teacher. It also revealed that students faced general problems such as being unsociable, introverted, and easily losing control. The study suggests that integrating positive psychology theory and collaborative learning approach can significantly enhance students’ self-emotional regulation ability. Key factors include fostering positive relationships with teachers and peers, focusing on strengths rather than weaknesses, and promoting personal growth. A safe and positive classroom environment, along with engaging activities such as group discussions, role-plays, jigsaw exercises, communication games, and Q&A sessions, can effectively enhance students’ ability to regulate their emotions.